Effect of diet particle size on utilization of sunflower oil seeds in nursery pig diets - G E Fitzner; T L Weeden; Robert H Hines; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred ninety-two weanling pigs were fed diets containing 15 or 25% sunflower oil seeds that were ground using a hammermill equipped with either a 1/8 or 3/16 in. screen. Average daily gain (ADG) of pigs fed the 25% sunflower seed diet ground through a 1/8 in. screen was similar to ADG of pigs fed the control diet or that with 15% sunflower seeds, although there was a reduction in ADFI. This indicates that finely ground sunflower seeds can be utilized in nursery pig diets up to 25% with no impairment in performance.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Nursery pigs; Sunflower seeds; Paricle size